Attitude toward own aging as a risk factor for cognitive disorder in old age: 12-year evidence from the ILSE study - Siebert, Jelena Sophie; Wahl, Hans-Werner; Degen, Christina; Schröder, Johannes (Psychology and aging, 2018)
Previous research has demonstrated the harmful impact of subjective aging processes (e.g., negative age self-stereotyping) on normal cognitive aging in different domains of cognitive functioning, such as memory, executive function, and fluid abilities. Recently, subjective aging has also been linked to important biomarkers of Alzheimer’s disease (AD) and dementia-related outcomes, indicating associations with pathological cognitive aging. With data from the Interdisciplinary Longitudinal Study of Adult Development and Aging (ILSE), the present study extends this research by examining the long-term effect of attitude toward own aging (ATOA) on expert-based clinical diagnosis of mild cognitive impairment (MCI) and AD in old age. In the study, 260 initially cognitively healthy participants with a mean age of 62.5 years were followed for 12 years. In the course of the study, 103 participants developed MCI and 14 received diagnosis of AD. Logistic regression models showed that baseline ATOA predicted future clinical diagnoses of MCI and AD 12 years later, while controlling for sociodemographic, genetic, and health variables. Although theoretically suggested, evidence for a mediating role of leisure-activity level and control beliefs was scarce. Our findings add to the emerging literature supporting negative views of aging as a risk factor for cognitive disorder in old age. (PsycINFO Database Record (c) 2018 APA, all rights reserved)